The people and place of al-Hattaba: a socio-temporal juncture - El-Sawy, Heba (AUC Knowledge Fountain, 2020)
This thesis focuses on a neighborhood located in Historic Cairo called al-Hattaba. It is a neighborhood that is located on the citadel wall, houses over 500 families, and is considered a buffer zone to the citadel with an urban fabric that speaks to a different time and place that has managed to survive, rupture and challenge our own perceptions of mainstream urban planning trends. I focus on rhythms of change and the experiences of temporality in the everyday as entry points into al-Hattaba and its people. The times of al-Hattaba cannot be reduced nor contained into a linear progression of events; but rather people’s experiences are temporally thick and multiplicitous, constituted in practices and relationships that traverse the past and anticipations of the future, narrated through the lived experiences of the present. I demonstrate how al-Hattaba reveals through an analysis of rhythms (speed, slowness, intensity) and experiences of duration (how time and its depth is experienced as long, short, near, distant, simultaneous, heterogeneous) many possibilities that can emerge and how people’s practices can change, alter, or challenge plans of urban renewal or development. This is what then allows me to describe the thesis as an exploration of the complex, ordinary, yet paradoxical relationship al-Hattaba and its people have with time, and how such a multiplicitous relationship has shaped the way the residents navigate and maneuver through disruptive events that threaten their everyday, histories, and futures. The way in which residents navigate their lives takes on many different manifestations, but a common thread through all of these navigations is the making of their everyday through a reworking of their relationship with time, space, and the social. Their relationship with time is evident in their oral histories, architecture of their homes, crafts, ovens, photographs, the urban fabric of their streets, their relationship with the historic monuments that surround them, and the Citadel and Citadel gate. This relationship with time is also marked in their daily interactions with each other, with different governmental institutions, and with Megawra BEC as well as other places outside of al-Hattaba to which el-Hattaba residents are connected.